NGO strategy, policy networks, and climate policymaking process in China - Zhang, Hao (Frontiers in Political Science, 2024)
This article examines the relationship between grassroots non-governmental organizations (NGOs) and the authoritarian state of China in terms of mobilizing policy changes in response to the climate crisis. It focuses on the advocacy strategy of NGOs and seeks to explain how NGOs in China use their expertise as the entry point to establish policy networks with the country's most influential policymakers and experts. Greenovation Hub (G:hub) is the case study for this investigation. To look into the interaction between G:hub and other experts within policy networks, I used the policy network framework that Teets (2018) initially applied in the Chinese context. I discovered that mutually aligned policy objectives are the key for the effectiveness of NGOs' expert advocacy strategy of constructing policy networks within the expert community in China. Cooperating with other experts can help NGOs to create an "insider" role for themselves. In addition, this research also discussed the conditions for NGO inclusion. I found opportunities and limitations linked to the alignment of NGOs' policy objectives with the state's vision for climate policy. The research conducted by NGOs also faced rejection if it failed to identify the state's priorities, highlighting the limitations of this approach. The significance of this finding is that the expertise strategy works for policy advocacy regardless of regime type, but that accessing policy networks is even more vital in a closed policymaking process. This case study further enhances the comprehension of the policy influence that NGOs have on the climatic effects of China's overseas development policies.